Effect of Dietary Chromium Supplementation on Performance and Carcass Traits of Broiler Chicks - Ghanbari, Shayan; Ebrahimnazhad, Yahya; Eshratkhah, Behrad; Nazeradl, Kambiz (Pakistan Journal of Nutrition, 2012)
This study investigated the effect of dietary supplementation of chromium from chromium picolinate source on the performance, carcass traits of broilers. Three hundred sixty one day old commercial male broilers (Ross 308) were randomly allocated to one of 24 floor pens in a completely randomized design with six treatment and four replicate groups and fifteen chicks per each pen. Dietary treatments consisted of 0 (control), 400, 800, 1200, 1600 and 2000 μg Cr per kg of basal diet. Feed intake, body weight gain and feed conversion ratio were measured during 1 to 21, 21 to 42 and 1 to 42 days of age. At 42 days of age two birds from each pen were selected and after weighing slaughtered and dissected manually. Carcass yield, liver, abdominal fat, pancreas, thighs and breast weight declared as percentage of live body weight. The results showed that performance of broilers was not affected by dietary supplemental chromium. Also supplementation of broiler diet didn't influence carcass traits. Nevertheless there is a non significant increase in liver and pancreas weight while increasing the Cr content of the diet. It can be concluded that chromium content of the basal starter and finisher diet and drinking water is adequate to normal requirement of broilers under such experimental conditions and supplementing of Cr may not be essential.